Kwe As Resurgent Method - Simpson, Leanne Betasamosake (Feminist Asylum: A Journal of Critical Interventions, 2022)
Like Dancing on Our Turtle’s Back and “Land as Pedagogy,” this book was generated from within Nishnaabeg intelligence — Nishnaabeg intellectual practices or, more broadly, Nishnaabewin — rather than the traditional theoretical and methodological orientations of the Western academy (Simpson 2014; 2013; 2011). It is anchored theoretically within the ways my people generate knowledge, through deep reciprocal embodied engagement with Aki, and by participating with full presence in embedded practices — inherent processes that occur within a series of ethical frameworks that, when adhered to, continually generate consent.